A software application for mapping livestock waste odour dispersion. (July 2015) - Danuso, Francesco; Rocca, Alvaro; Ceccon, Paolo; Ginaldi, Fabrizio
Abstract: In developed Countries, coexistence of livestock production and urban settlements is a source of problematic interactions that are regulated by specific legislation, often requiring the evaluation of the potential environmental impact of livestock odour emissions. For this purpose, dispersion models are powerful tools that can be classified as dynamic (Eulerian and Lagrangian) or static (Gaussian). The latter, while presenting some limitations in condition of wind calm and complex orography, are widely adopted for their ease of use. OdiGauss is a free multilingual software application allowing to estimate odour dispersion from multiple point sources and to generate the related maps. Dispersion is calculated according to a Gaussian approach, as a function of wind speed and direction, precipitation, temperature, and solar radiation. OdiGauss incorporates a model of odour emissions from poultry farms ( EmiFarm ) which makes predictions based on manure production and management. Two case studies of software application on real poultry and swine farms are presented. Highlights: OdiGauss software simulating odour dispersion from livestock is presented. OdiGauss is fast and easy to use allowing climatological evaluation of dispersion. An example model providing dynamic emissions to OdiGauss is also included. Easy meteo data importing and exporting of dispersion maps in common GIS formats.